Knowledge about First Aid among Medical, Nursing and Allied Health Sciences Students of Rawalpindi Medical University, Pakistan. - Rasool, Tayyab; Haroon Janjua, Muhammad Ahmed; Ahmad, Zeeshan; Gul, Sanabil; Sarwar, Aneeqa; Fahim, Wajeeha; Bajwa, Mahnoor; Faheem, Saleha (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Background: First aid is an important life-saving skill that can make a profound impact in emergency situations. It involves giving rapid medical care at the site of the accident. Medical and nursing students often get training inside controlled hospital environments. However, the scope of first aid education entails effectively responding to many emergency situations outside the hospital. Objectives: The objective of this study is to assess the knowledge of undergraduate students in the fields of MBBS, Nursing, and Allied Health Sciences (AHS) with regards to first aid. Materials and Method: A cross-sectional questionnaire-based study was conducted from April 2023 to August 2023 at Rawalpindi Medical University. A validated, self-structured 16 items questionnaire regarding first aid was used to assess the knowledge of the students. Data analysis was done using Microsoft Excel and SPSS version 26. Results: The study included a total of 309 individuals enrolled in the MBBS, AHS, and Nursing programs. The mean knowledge score among all students was 8.72 ± 1.878. Only 10 (3.23%) students had High knowledge, 216 (69.9%) students had Moderate knowledge, and 83 (26.8%) students had Low knowledge of first aid. Significant differences were observed in knowledge scores among degree programs, with MBBS students (M = 9.02, SD = 1.61) scoring significantly higher than AHS (M = 8.0, SD = 2.33) and Nursing students (M = 8.06, SD = 2.11). However, no significant difference was found between AHS and Nursing students. A positive correlation was identified between academic year and knowledge scores, indicating increasing proficiency with each academic year. Conclusion: This study sheds light on the current state of first aid knowledge among undergraduate healthcare students and underscores the need for tailored educational strategies to equip them with the essential knowledge for effective emergency response.